cis-Diastereoselective synthesis of chroman-fused tetralins as B-ring-modified analogues of brazilin - Gogoi, Dimpee; Devi, Runjun; Pahari, Pallab; Sarma, Bipul; Das, Sajal Kumar (Beilstein Journal of Organic Chemistry, 2016)
We have synthesized a series of cis-6a,7,8,12b-tetrahydro-6H-naphtho[2,1-c]chromen-6a-ols as B-ring-modified analogues of (±)-brazilin. A completely regio- and cis-diastereoselective intramolecular Friedel–Crafts epoxy–arene cyclization of 1-tetralone-derived glycidyl ethers catalyzed by Brønsted acids was used as the key step. Our worries concerning the formation of cis–trans product mixtures and their probable conversion to naphthopyran derivatives via dehydration of the tertiary hydroxy group were laid to rest. Additionally, the angular hydroxy group of one of the synthesized products has been reductively removed by a diastereoselective method which should be useful in future for preparing libraries of chroman-fused tetralins with trans-stereochemistry at the ring junction.
Keywords: brazilin; chroman; epoxy-arene cyclization; natural-product-like molecules; tetralin